THE INFLUENCE OF KOREAN WAVE, BRAND AMBASSADOR, AND BRAND IMAGE ON PURCHASE INTENTION OF SOMETHINC SKINCARE PRODUCTS IN MANADO - Jeify Lioni Agustin Suwuh; Paulus Kindangen; Regina Trifena Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Abstract: The purpose of this research is to analyze the influence of Korean wave, brand ambassador, brand image on purchase intention of Somethinc skincare product in Manado simultaneously or partially. The research variables consist of, Xâ‚ is Korean wave, Xâ‚‚ is Brand ambassador, Xâ‚ƒ is Brand image and Y is Purchase Intention. Research data is primary data, obtained from the results of the distribution of questionnaires design with the likert scale. The sample of the research was the female and user skincare in Manado. Test instruments using Validity and Reliability Test using SPSS. Technique Analysis, Multiple regression, Classic Assumption Test, Hypothesis Test (F-Test and t-Test). The result showed that Korean wave has negative effect on Purchase Intention, while Brand ambassador and Brand image has positive effect on Purchase Intention.